Pengaruh Mutu Layanan Sarana dan Prasarana Terhadap Kepuasan Mahasiswa di Fakultas Pendidikan Teknologi dan Kejuruan Universitas Pendidikan Indonesia - Purwandani, Dela; Sutarsih, Cicih; ., Sururi (UPI, 2016)
The research titled â The Effect Quality of Service Infrastructures to the satisfaction ofÂ students in the Faculty of Technology and Vocational Education University ofÂ Indonesiaâ. Issues addressed in this study is about how satisfied students are influencedÂ by the quality of the service facilities and infrastructure. Generally, this study aims to findÂ out the true picture regarding the quality of infrastructure services to the satisfaction ofÂ students in FPTK UPI. The method used in this research is descriptive method withÂ quantitative approach. The technique of collecting data using questionnaires that wereÂ distributed to 96 students as the study sample. The result of the calculation using theÂ general trend show that student satisfaction in the high category with an average scoreÂ of 3.43 and quality of services in environmental infrastructure FPTK UPI included in theÂ high category with an average score of 3.51. The correlation analysis using PearsonÂ Product Moment, the correlation coefficient between variables X and Y is equal to 0.786Â which shows that the correlation between the two variables are at high-level relations.Â The results of the significance test that is 12,320>1,661, it means that the correlationÂ coefficient between variables X and Y are significant with linear regression analysisÂ equation that is:Â Å¶ = 9,661 + 0,806 X, this means that any change in one unit variable X will be followedÂ by a change of variable Y for 0,806. It is concluded that there is a positive and significantÂ relationship of Quality of Service Infrastructures on Student Satisfaction in FPTK UPI. The need to improve on the quality of service that is the responsiveness of the serviceÂ while in terms of student satisfaction is the fulfillment of infrastructure for studentÂ activities.